Geometric design of two novel rotor profiles for Roots vacuum pumps with elliptical curve - Zhengqing Li; Xiaojun Wang; Xianhu Han; Yuhong Cai (Results in Engineering)
Rotors are the key components of Roots vacuum pumps owing to their significant impact on compression ratio and volume utilization rate of the product, which is formed on the rotor profile. This study proposes two novel elliptical rotor profiles: one designed with an elliptical curve at the top and the other with an elliptical curve at the waist. Mathematical models of the new rotor profiles were established, and profile equations were derived on a geometric method. To examine their shapes and characteristics, the rotor profiles were designed with a pumping speed of 70 L/s for the Roots vacuum pumps. Additionally, a two-dimensional numerical simulation of the two novel rotors was conducted to analyze the flow field of the Roots vacuum pumps. The results indicated that the top elliptical rotor profile had the advantage of a high-volume utilization rate approaching 55 %, whereas the waist rotor profile had the advantage of a high effective pumping speed, exceeding the top elliptical rotor profile by a factor of 1.5.